2015
DOI: 10.1074/jbc.m114.619643
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Confinement Plays a Pivotal Role in Regulating Neutrophil-generated Tractions, Speed, and Integrin Utilization

Abstract: Background: Neutrophils must generate well regulated forces to migrate within the confined, three-dimensional space of diseased tissues. Results: Spatial confinement induces a switch to integrin-independent motility, but integrins regulate three-dimensional traction force generation. Conclusion: Physical confinement is sufficient to induce integrin-independent motility. Significance: Spatially confined double hydrogels are a biomimetic system that may allow for ex vivo testing of neutrophilspecific therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 40 publications
(54 reference statements)
6
48
0
Order By: Relevance
“…Such behavior is indicative of a contractile, integrin-dependent mode of motility as opposed to a pushing, or integrin-independent mechanism (38). These observations are consistent with recent findings showing that integrins continue to play a significant regulatory role for traction generation and motility under confinement in the presence of ligands (39). Using the simple MDM, we detect statistically significant differences between naïve and LPS-activated human neutrophils.…”
Section: Mdmsupporting
confidence: 81%
See 2 more Smart Citations
“…Such behavior is indicative of a contractile, integrin-dependent mode of motility as opposed to a pushing, or integrin-independent mechanism (38). These observations are consistent with recent findings showing that integrins continue to play a significant regulatory role for traction generation and motility under confinement in the presence of ligands (39). Using the simple MDM, we detect statistically significant differences between naïve and LPS-activated human neutrophils.…”
Section: Mdmsupporting
confidence: 81%
“…Confocal image stacks of 512 × 512 × 128 voxels (108 × 108 × 38 μm 3 ) were recorded every 2-3 min with a z-step of 0.30 μm. To ensure physiological imaging conditions within the imaging chamber, temperature was controlled at 37°C as previously described (17,39). For reflectance microscopy, an APO 40× water immersion objective (NA = 1.15; Nikon) with z-step = 0.25 μm was used to obtain typical imaging volumes of 167 × 167 × 81 voxels (52 × 52 × 20 μm 3 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that in vivo talin is not required for neutrophil motility (Lammermann et al, 2013); however in 3D in vitro gels, neutrophil directed migration to a gradient of chemoattractant was impaired in talin-deficient neutrophil-like cells (Yamahashi et al, 2015). Interestingly, in a more recent study, Toyjanova et al showed that spatial confinement of neutrophils is sufficient to cause a switch to integrin-independent motility (Toyjanova et al, 2015), It has also been shown that in similar confined environments mesenchymal cancer cells are capable of adopting a fast moving amoeboid-like mode of migration (Liu et al, 2015b). This finding might provide insight into the mesenchymal to amoeboid transition seen in some migrating cancer cells (Friedl and Wolf, 2003), and raises interesting questions about the role of a uropod-like rear in the more rapid migration of cancer cells.…”
Section: Signaling and The Neutrophil Uropodmentioning
confidence: 99%
“…Actin polymerization in the leukocyte elicits pulling and pushing forces that support the movement through the confined endothelial pore. [63][64][65] The docking structure A widely observed phenomenon associated with leukocyte TEM is the formation of endothelial membrane protrusions rich in Filamentous (F)-actin that surround transmigrating leukocytes. These endothelial structures were first described by Barreiro and colleagues who defined them as docking structures.…”
Section: Paracellular and Transcellular Migrationmentioning
confidence: 99%